Penerapan Model Pembelajaran Problem Based Learning (PBL) terhadap Sikap Ilmiah Siswa dalam Pembelajaran Biologi Kelas XI IPA SMAN 4 Pekanbaru Tahun Ajaran 2013/2014 - Apriliana, Vina; Yustina, Yustina; syafii, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: There have been studies to determine the application of the learning model of Problem-Based Learning (PBL) to the scientific attitude of students in learning biology class XI IPA SMAN 4 Pekanbaru in Academic Year 2013/2014. Research was conducted in May 2014 with a sample of students of class XI IPA 1 (control class) by the number of students 33 and XI IPA 4 (experiment class) by the number of students 32. The parameters used in the study of critical attitude, honest, open, conscientious and earnest. Collecting data using a scientific attitude observation sheet. Average scientific attitude in the experimental class was 84.39% in both categories, while the control class with 40.69% less category. Based on the research results, it can be concluded that there are differences between the scientific attitude of students using the experimental class learning model PBL in the learning process in comparison with the control class learning using lecture and discussion.Key words: scientific attitudes, high school senior, problem-based learning